Notifiche
Cancella tutti

Mi potete aiutare esercizio n 267

  

0
CAPTURE 20250214 213906
Autore
2 Risposte



2

(((48^2/6^2/4^2 - 6^6/6^6)^2)^2 + (7^5/7^3 - 40))^3/90^3=

=(((2^8·3^2/(2^2·3^2)/2^4 - 1)^2)^2 + (7^2 - 40))^3/90^3=

=(((2^6/2^4 - 1)^2)^2 + (49 - 40))^3/90^3=

=(((4 - 1)^2)^2 + 9)^3/90^3=

=(9^2 + 9)^3/90^3= 90^3/90^3= 1



1
CAPTURE 20250214 213906

=============================================================

$\small \left\{\left[\left(48^2 : 6^2 : 4^2-6^6 : 6^6\right)^2\right]^2+\left(7^5 : 7^3-40\right)\right\}^3 : 90^3=$

$\small =\left\{\left[\left(2304 : 36 : 16 -1\right)^2\right]^2+\left(7^{5-3}-40\right)\right\}^3 : 90^3=$

$\small =\left\{\left[\left(4 -1\right)^2\right]^2+\left(7^2-40\right)\right\}^3 : 90^3=$

$\small =\left\{\left[3^2\right]^2+\left(49-40\right)\right\}^3 : 90^3=$

$\small =\left\{3^{2×2}+9\right\}^3 : 90^3=$

$\small =\left\{3^4+9\right\}^3 : 90^3=$

$\small =\left\{81+9\right\}^3 : 90^3=$

$\small =90^3 : 90^3= 1$



Risposta
SOS Matematica

4.6
SCARICA